Digital Content and the Problem of Excellence in Neoliberal Culture - Godínez-Burgos , Emmanuel (2023)
Digital content platforms show multiple individuals performing activities that can be qualified as frivolous or dangerous. This article examines the problem of digital content creation that abandons the idea of excellence, approaching it from the notion of practice and the development of internal goods to it, proposed by MacIntyre (2004), and from the critique of individualism in contemporary culture. It is argued that digital content creators' disregard for excellence, within the framework of neoliberalism, represents a form of individualistic success that corrupts practices and erodes their sense of community.